A randomised trial to compare the safety, tolerability and efficacy of three drug combinations for intermittent preventive treatment in children. - Kalifa Bojang; Francis Akor; Ousman Bittaye; David Conway; Christian Bottomley; Paul Milligan; Brian Greenwood (PLoS ONE)
Background Results from trials of intermittent preventive treatment (IPT) in infants and children have shown that IPT provides significant protection against clinical malaria. Sulfadoxine-pyrimethamine (SP) given alone or in combination with other drugs has been used for most IPT programmes. However, SP resistance is increasing in many parts of Africa. Thus, we have investigated whether SP plus AQ, SP plus piperaquine (PQ) and dihydroartemisinin (DHA) plus PQ might be equally safe and effective when used for IPT in children in an area of seasonal transmission. Methods During the 2007 malaria transmission season, 1008 Gambian children were individually randomized to receive SP plus amodiaquine (AQ), SP plus piperaquine (PQ) or dihydroartemisinin (DHA) plus PQ at monthly intervals on three occasions during the peak malaria transmission season. To determine the risk of side effects following drug administration, participants in each treatment group were visited at home three days after the start of each round of drug administration and a side effects questionnaire completed. To help establish whether adverse events were drug related, the same questionnaire was administered to 286 age matched control children recruited from adjacent villages. Morbidity was monitored throughout the malaria transmission season and study children were seen at the end of the malaria transmission season. Results All three treatment regimens showed good safety profiles. No severe adverse event related to IPT was reported. The most frequent adverse events reported were coughing, diarrhoea, vomiting, abdominal pain and loss of appetite. Cough was present in 15.2%, 15.4% and 18.7% of study subjects who received SP plus AQ, DHA plus PQ or SP plus PQ respectively, compared to 19.2% in a control group. The incidence of malaria in the DHA plus PQ, SP plus AQ and SP plus PQ groups were 0.10 cases per child year (95% CI: 0.05, 0.22), 0.06 (95% CI: 0.022, 0.16) and 0.06 (95% CI: 0.02, 0.15) respectively. The incidence of malaria in the control group was 0.79 cases per child year (0.58, 1.08). Conclusion All the three regimens of IPT in children were safe and highly efficacious Trial registration ClinicalTrials.gov NCT00561899.